Cloninger Type 2 Score and Lesch Typology Predict Hospital Readmission of Female and Male Alcohol‐Dependent Inpatients During a 24‐Month Follow‐Up. (20th September 2017) - Weinland, Christian; Braun, Birgit; Mühle, Christiane; Kornhuber, Johannes; Lenz, Bernd
Abstract : Background: Relapse after detoxification treatment is a common problem in alcohol dependence. However, its prediction still lacks reliability. We here investigated whether the easily accessible clinical Cloninger and Lesch classifications predict alcohol‐related hospital readmission following inpatient withdrawal treatment. Methods: In this bicentric prospective clinical study, 67 female and 84 male alcohol‐dependent inpatients were characterized according to the Cloninger items and the Lesch typology. The patients' records were followed for 24 months. Because of the well‐established sex differences in alcohol dependence, we studied females and males separately. Results: Overall, 54% of the female patients and 67% of the male patients sustained at least 1 alcohol‐related hospital readmission during the follow‐up. Readmission was related to a higher Cloninger type 2 score than nonreadmission (females, p  = 0.007, males p  = 0.044). In females, the Cloninger type 2 score correlated with the number of readmissions ( ρ  = 0.384, p  = 0.001) and the days to first readmission ( ρ  = −0.333, p  = 0.006). The effects were stronger in patients with age at onset of alcohol dependence over 25 years. We found gender dimorphisms concerning the Cloninger items. In female patients, the 4 Lesch subtypes differed in their risk ( p  = 0.010), the number ( p  = 0.040), and the days to first readmission ( p  = 0.031). Lesch type 1 was associated with an increased risk (OR = 4.83, p  = 0.041) and Lesch type 2 with a reduced risk (OR = 0.07, p  = 0.004). In addition, the number of previous inpatient alcohol withdrawals predicted the patients' outcomes ( p  < 0.05). Conclusions: The Cloninger type 2 score and the Lesch typology are promising tools for the prediction of alcohol‐related readmissions. Our findings provide the basis to optimize relapse prevention in alcohol dependence.